Pengaruh penggunaan spalk bermotif pada pemasangan infus terhadap kecemasan anak usia prasekolah - Nanda Riyani Putri; Komala Sari; Liza Wati; Meily Nirnasari (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Data from the World Health Organization (2022) shows that around 80% of children treated in hospitals undergo invasive procedures such as IV insertion, and more than 60% of them show signs of anxiety. In Indonesia, the 2023 Mother and Child Health Survey recorded that 74.8% of children experienced moderate to severe anxiety during medical treatment. Preschool-aged children are particularly vulnerable to anxiety due to their limited ability to express their fears when facing medical procedures. Purpose: To determine the effect of using patterned splints on anxiety in preschool-aged children. Method: The study population consisted of all preschool-aged children treated in the Flamboyan Room over the past two months, totaling 55 children. A sample of 17 children was selected using purposive sampling with a quasi-experimental pre-test and post-test design without a control group. The instrument used was the Taylor Manifest Anxiety Scale (T-MAS) questionnaire, which had been tested for validity with 27 valid statements (r > 0.444) and high reliability (α = 0.965). Results: The study shows that before the intervention, most children (52.9%) experienced severe anxiety, and after the intervention, the majority of children (58.8%) experienced mild anxiety. Statistical testing using the Wilcoxon Signed Ranks Test showed a p-value = 0.001, which means that there is a significant effect of using patterned splints on reducing children's anxiety levels. Conclusion: Based on these results, patterned splints are effective in reducing children's anxiety levels and are suitable as a non-pharmacological intervention based on atraumatic care. Suggestion: Researchers recommend the procurement and development of standard operating procedures (SOPs) for the use of patterned splints and the development of supporting innovations such as character dolls, picture books, or educational shows to create a child-friendly care environment